Genome methylation and regulatory functions for hypoxic adaptation in Tibetan chicken embryos - Yawen Zhang; Wenyu Gou; Jun Ma; Hongliang Zhang; Ying Zhang; Hao Zhang (PeerJ, 2017)
Tibetan chickens have unique adaptations to the extreme high-altitude environment that they inhabit. Epigenetic DNA methylation affects many biological processes, including hypoxic adaptation; however, the regulatory genes for DNA methylation in hypoxic adaptation remain unknown. In this study, methylated DNA immunoprecipitation with high-throughput sequencing (MeDIP-seq) was used to provide an atlas of the DNA methylomes of the heart tissue of hypoxic highland Tibetan and lowland Chahua chicken embryos. A total of 31.2 gigabases of sequence data were generated from six MeDIP-seq libraries. We identified 1,049 differentially methylated regions (DMRs) and 695 related differentially methylated genes (DMGs) between the two chicken breeds. The DMGs are involved in vascular smooth muscle contraction, VEGF signaling pathway, calcium signaling pathway, and other hypoxia-related pathways. Five candidate genes that had low methylation (EDNRA, EDNRB2, BMPR1B, BMPRII, and ITGA2) might play key regulatory roles in the adaptation to hypoxia in Tibetan chicken embryos. Our study provides significant explanations for the functions of genes and their epigenetic regulation for hypoxic adaptation in Tibetan chickens.